Control interno de los ingresos de la empresa DATAPRO S.A., período 2019-2020 - Varas Valencia, Stalyn Alexander (2021)
This research was carried out in the company Datapro SA, of the city of Guayaquil, dedicated to the commercialization of products of technological solutions such as computers, scanners, printers, plotters, cameras, and other peripheral accessories, through a qualified work team and committed to providing customer service with the highest quality standards. The research objective was to evaluate the internal control of income for the 2019-2020 period, since it presented a significant decrease in its sales, due to various risk factors such as empirical management, weak control, poor organizational structure, and the effects of Covid-19 pandemic that caused a loss of market share and the ability to meet its obligations in a timely manner. The applied methodology had a mixed approach, which accompanied by the type of descriptive research and with the use of the deductive method, it was possible to analyze in detail particular aspects related to the issue raised. In addition, the techniques of interview directed to the executive personnel were used, and the direct observation of the financial statements was collected the necessary data that support the purpose of this case study. The results found were that due to the weak organizational structure the internal processes tend to be delayed, in addition to the deficient control of income, some commercial transactions do not have the due documentary support and the study of the financial statements and added to the effects of the The pandemic showed the economic problems facing the company.